Molecular characterization and information entropies of chevron-like graphene nanoribbons with chemical applications - S. Manikanda Prabhu; A. R. Vijayalakshmi; S. Govardhan; S. Prabhu (Scientific Reports)
Abstract Carbon-based nanomaterials, such as graphene and graphene nanoribbons (GNRs), have attracted researchers because of their optoelectronic properties. One of the most intriguing properties of GNRs is their tunable bandgap. Unlike inherently metallic graphene sheets, GNRs can exhibit a bandgap, a crucial property for electronic devices. By controlling the width and edge configuration of GNRs, researchers can precisely tailor their electronic properties to meet specific requirements. Chevron-like graphene nanoribbons (ChGNRs) are a class of nanomaterials with unique properties due to their wavy morphology. The electrical conductivity of ChGNRs makes them potentially useful in devices like organic solar cells and transistors. In this study, we computed the Shannon’s information entropy measures of ChGNRs using a variety of degree-based topological descriptors (TDs). The basic graph theoretical approach was utilized to derive the explicit mathematical equations of the TDs for the ChGNRs. The results were compared with cove-edged graphene nanoribbons (cGNRs) to analyze the thermodynamic stability of both ChGNRs and cGNRs and the different trends were pointed out.